1998
DOI: 10.1097/00006123-199810000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Familial Cerebral Aneurysms

Abstract: The prevalence of aneurysms is significantly elevated in family members of people with asymptomatic aneurysms. It is suggested that familial asymptomatic aneurysms are more likely to rupture in families having members with aneurysmal subarachnoid hemorrhage than in those without.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 17 publications
3
16
0
4
Order By: Relevance
“…In second-degree relatives, the incidence of SAH is similar to that found in the general population (Bromberg et al 1995). It has also been shown that the prevalence of unruptured IA is significantly higher (10.5-13.5%) in a Japanese subgroup with a family history of IA Kojima et al 1998). The prevalence of harboring an IA within the population aged over 30 years is between 3.6 and 6.5% (Ujiie et al 1993;Yamaki et al 1994;Iwamoto et al 1999;Wardlaw and White 2000).…”
Section: Pathology Epidemiology and Etiologysupporting
confidence: 73%
“…In second-degree relatives, the incidence of SAH is similar to that found in the general population (Bromberg et al 1995). It has also been shown that the prevalence of unruptured IA is significantly higher (10.5-13.5%) in a Japanese subgroup with a family history of IA Kojima et al 1998). The prevalence of harboring an IA within the population aged over 30 years is between 3.6 and 6.5% (Ujiie et al 1993;Yamaki et al 1994;Iwamoto et al 1999;Wardlaw and White 2000).…”
Section: Pathology Epidemiology and Etiologysupporting
confidence: 73%
“…Eight of 70 patients had a family history, and 4 of 28 patients with aneurysm growth had a family history, suggesting that family history was not significant (11). The prevalence of asymptomatic aneurysms in families with aneurysmal SAH was 4.3% and significantly lower than that in the families without aneurysmal SAH, suggesting that asymptomatic aneurysms are more likely to rupture in patients with familial aneurysmal SAH, and, because familial aneurysms are more likely to rupture at smaller size and younger age than nonfamilial aneurysms (14), great care must be taken to monitor changes in size at regular intervals (13).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, aneurysms that do rupture tend to rupture at a younger age and at a smaller diameter among patients with FIA (Bacigaluppi et al 2013; Broderick et al 2009; Lozano and Leblanc 1987). Along with the increased risk for aneurysm formation and rupture, patients with FIA appear to have a poorer outcome after rupture (Bromberg et al 1995; Kojima et al 1998). Generally, screening with magnetic resonance angiography (MRA) or computerized tomographic angiography (CTA) is recommended for individuals with two or more first-degree relatives diagnosed with intracranial aneurysms (Bor et al 2010, 2014; Brisman et al 2006; Brown et al 2008; Ronkainen et al 1998; Thompson et al 2015).…”
Section: Introductionmentioning
confidence: 99%